Mitigation of divertor heat flux by high-frequency ELM pacing with non-fuel pellet injection in DIII-D. (August 2017) - Bortolon, A.; Maingi, R.; Mansfield, D.K.; Nagy, A.; Roquemore, A.L.; Baylor, L.R.; Commaux, N.; Jackson, G.L.; Lunsford, R.; Lasnier, C.J.; Makowski, M.J.; Nazikian, R.; et al.
Abstract: Experiments have been conducted on DIII-D investigating high repetition rate injection of non-fuel pellets as a tool for pacing Edge Localized Modes (ELMs) and mitigating their transient divertor heat loads. Effective ELM pacing was obtained with injection of Li granules in different H-mode scenarios, at frequencies 3–5 times larger than the natural ELM frequency, with subsequent reduction of strike-point heat flux (Bortolon et al., Nucl. Fus., 56, 056008, 2016). However, in scenarios with high pedestal density (∼6 × 10 19 m −3 ), the magnitude of granule triggered ELMs shows a broad distribution, in terms of stored energy loss and peak heat flux, challenging the effectiveness of ELM mitigation. Furthermore, transient heat-flux deposition correlated with granule injections was observed far from the strike-points. Field line tracing suggest this phenomenon to be consistent with particle loss into the mid-plane far scrape-off layer, at toroidal location of the granule injection.